The Revolver in the Hive - Hundley, Nicolas (Book collections on Project MUSE., 2013)
This book takes place in the aftermath of tragedy, where grief is recognizable but contorted into unsettling forms. These poems chronicle with honesty - and bitter humor - a harrowing journey through loss, death, and mourning.